PERAN KEPUASAN DALAM MEMEDIASI PENGARUH KOMUNITAS MEREK TERHADAP LOYALITAS PENGGUNA HARLEY-DAVIDSON DI KOTA DENPASAR - I Gede Nandya Oktora Panasea; Ni Wayan Sri Suprapti (Faculty of Economics and Business Udayana University, 2013)
This study empirically explores the influences of brand community on loyalty when mediated by satisfaction. The data on this research were collected from observation, interviews, and questionnaires.Data analysis methods that used on this research were descriptive and inferential statistics. Descriptive statistics such as frequency distributions were used to describes the characteristics of the respondents, while inferential statisticssuch as Baron and Kenny Steps and Sobel test is used to test the hypotheses. The results showed that satisfaction partially mediates the effect of brand community on loyalty of Harley-Davidson users inDenpasar. It shows that satisfaction is an essential element for the brand community to realize the brand loya lty.